ASTRAGALIN, THE ACTIVE COMPONENT OF ALPINIA NIGRA AND ITS EFFECT ON TEGUMENTAL ULTRASTRUCTURE OF FLUKE PARASITE, FASCIOLOPSIS BUSKI - ANANTA SWARGIARY (International Journal of Pharma and Bio Sciences, 2015)
Alpinia nigra belonging to the family Zingiberaceae is an ethnomedicine with established anthelmintic property. In view of its medicinal property, the present study was designed to investigate the anthelmintic property of astragalin, a bioactive compound of A. nigra against fluke parasite, Fasciolopsis buski. In vitro exposure of flukes at varying concentrations 0.025 – 0.1 mg/ml of PBS a dose-dependent effect on motility and mortality was observed. Stereoscan observations of the astragalin exposed fluke revealed deformity of the surface architecture including shrinkage and eroded scales leading to scar formation as well as loss of the scales. Ultrastructural observations revealed distortion of glycocalyx, musculature region, basal layer and disintegration of the nucleus, nucleolus, nuclear membrane, Golgi complexes and mitochondria. A large number of vacuole formations could also be seen in flukes exposed to astragalin compared to control. The result therefore indicates the anthelmintic property of astragalin, the bioactive compound of A. nigra against the fluke parasite F. buski.